2008
DOI: 10.1080/15332960802125932
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Satisfied and Affectively Committed Clients' Lack of Referral Intent

Abstract: Satisfied and affectively committed clients are likely to refer their service providers to other consumers. Some devoted clients, however, seldom or never offer word-of-mouth (WOM) recommendations. Using the theory of planned behavior (TPB) and structural equation modeling, we found that negative attitudes toward giving referrals and perceptions of limited control over referral-giving were associated with reduced referral intentions for satisfied and affectively committed clients. The theoretical implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Positive word-of-mouth describes favorable communications regarding a certain firm that a customer is willing to share with others. Positive word-of-mouth has been shown to increase as customer commitment increases (Brown et al, 2005;Hagenbach et al, 2008;Harrison-Walker, 2001) and the longer the duration of time is anticipated to strongly moderate this positive relationship. Customers who feel a bond with a firm often become an advocate (Du et al, 2007).…”
Section: Commitment and Relational Behaviorsmentioning
confidence: 89%
“…Positive word-of-mouth describes favorable communications regarding a certain firm that a customer is willing to share with others. Positive word-of-mouth has been shown to increase as customer commitment increases (Brown et al, 2005;Hagenbach et al, 2008;Harrison-Walker, 2001) and the longer the duration of time is anticipated to strongly moderate this positive relationship. Customers who feel a bond with a firm often become an advocate (Du et al, 2007).…”
Section: Commitment and Relational Behaviorsmentioning
confidence: 89%
“…Yet, as demonstrated in the organizational behavior literature, commitment and intent are not the same thing, and often commitment is seen as an antecedent to intent (e.g., intent to turnover) (Ferres et al, 2003, Bailey, 2006, Hagenbuch et al, 2008, Høie et al, 2010, Spitzmüller and Stanton, 2006, van Breukelen et al, 2004. Following the lead from organizational behavior research, we propose that past commitment to the internationalization process is a precursor to the intent to further internationalize.…”
Section: Commitment To Internationalizationmentioning
confidence: 88%
“…Therefore, we hypothesize the following: Hypothesis 3. Corporate brand pride emotions have a positive influence on attitudinal corporate brand pride Linking attitudinal corporate brand pride and WOM/Employee referrals Previous research on brand supporting behavior such as WOM and (employee) referrals identified multiple antecedents, such as brand passion (Albert et al, 2013), positive emotions (Lovett et al, 2013), satisfaction (Hagenbuch et al, 2008;Wangenheim & Baón, 2007), brand commitment (Albert et al, 2013), product (Wangenheim & Baón, 2007;Wolny & Mueller, 2013) or brand involvement (Wolny & Mueller, 2013). WOM can be defined as "informal, person-to-person communication between a perceived non-commercial communicator and a receiver regarding a brand, a product, an organization, or a service" (Harrison, 2001, p.63).…”
Section: Linking Perceived Negative Corporate Brand Publicity and Emo...mentioning
confidence: 99%